Measurements of a rectangular jet - Chan, Yen Shun. (2009)
In this project, the flow characteristics of an unconfined rectangular jet, aspect ratio 20 running at velocity of 25m/s is being investigated. The results obtained shows that the flow was able to achieve self similar in the mixing layer at x/D= 4 for both Umean and Urms profile for the single wire experiments. Self preservation occurred at x/D=6 for the Umean profile in the interaction region while the Urms profile was unable to show any self preservation.